Peritectic phase formation kinetics of directionally solidifying Sn-Cu alloys within a broad growth rate regime. (November 2021) - Mehreen, Syeda U.; Nogita, Kazuhiro; McDonald, Stuart D.; Yasuda, Hideyuki; StJohn, David H.
Abstract: Previous studies have shown that the peritectic transformation may not occur and, depending on the cooling rate, the peritectic phase can nucleate and grow directly from the melt. This study investigates the effect of growth rate (pull rate) on a peritectic alloy via in-situ directional solidification, in particular where rapid solidification dramatically alters the microstructure, whereby only the peritectic phase nucleates directly from the liquid. The phase formation events occurring during the directional solidification of a Sn-Cu peritectic alloy were studied, confirming that growth rate has a critical effect on the phase selection of the Sn-10 wt %Cu alloy. Over the range of growth rates studied, competitive nucleation between the pro-peritectic Cu3 Sn phase and the peritectic Cu6 Sn5 phase occurs, and beyond a critical growth rate, nucleation of the Cu3 Sn phase does not occur and the Cu6 Sn5 phase nucleates preferentially from the metastable liquid. Phase competition in peritectic alloys is of interest from not only a fundamental perspective but also from a practical viewpoint allowing for unique microstructure design. This work presents for the first time the in-situ directional solidification of a Sn-Cu alloy that involves an equilibrium peritectic reaction and shows the effect of growth rate on phase selection. Furthermore, this study has confirmed that the peritectic transformation does not occur in the investigated Sn-Cu alloy for the range of conditions examined. Graphical abstract: Image, graphical abstract